2014
DOI: 10.1080/09542299.2014.11073965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotoxic and oxidative stress response to dimethoate in freshwater fish Channa punctatus (Bloch)

Abstract: Dimethoate is one of the organophosphate insecticides widely used in agriculture throughout the world and is an inhibitor of cholinesterase in animals. The objective of the present study was to detect oxidative stress and DNA damage induced by dimethoate in the freshwater fish Channa punctatus (C. punctatus). The LC 50 -96 h value of technical grade dimethoate was estimated at 19.10 µg L -1 in a semi-static system and, on the basis of the LC 50 value, three concentrations were determined. The fish were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…The decrease in MN formation observed after day 7 with doses of 4.52 and 11.30 mg/L NPK and after day 14 for 2.26 mg/L NPK may be attributed to the repair of damaged cells. Similar repair mechanisms have been reported in freshwater fish species exposed to different toxicants (Ali et al 2014;Ismail et al 2018;Nwani et al 2017).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The decrease in MN formation observed after day 7 with doses of 4.52 and 11.30 mg/L NPK and after day 14 for 2.26 mg/L NPK may be attributed to the repair of damaged cells. Similar repair mechanisms have been reported in freshwater fish species exposed to different toxicants (Ali et al 2014;Ismail et al 2018;Nwani et al 2017).…”
Section: Discussionsupporting
confidence: 82%
“…The MN assay is preferred to other sensitive assays because it does not require killing of the fish specimen (Kumar et al 2013; Nwani et al 2014). It is also simple, rapid, consistent, and takes minimal time to complete (Ali et al 2014; Ajima et al 2020). Durgo et al (2009) observed free radical formation and significant DNA damage in human leucocytes exposed to wastewater from fertilizer factories.…”
mentioning
confidence: 99%
“…DNA damage was also observed in the gill cells of the European eel (Anguilla anguilla) exposed to the OP glyphosate (Guilherme et al 2012). Ali et al (2014) also reported the time-dependent and dose-dependent increase of genotoxicity of an OP insecticide, dimethoate in C. punctatus, which were found to be highly correlated with oxidative stress. Our results along with those of Pamanji et al (2015) mentioned earlier, provide information on the toxic effects of MCP in both the adults and embryos of zebrafish suggesting that MCP can affect zebrafish at any time during its life cycle.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have found a direct relationship between the occurrence of lipid peroxidation (LPO) and DNA damage expressed as MN presence (Ali et al 2014 ; Nwani et al 2010 ). In the present study, the occurrence of lipid peroxidation and liver histopathological alterations were observed in A. gr.…”
Section: Discussionmentioning
confidence: 99%